2019
DOI: 10.24869/psyd.2019.413
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injury in Adolescents: A Five-Year Study of Characteristics and Trends

Abstract: Background: Adolescent non-suicidal self-injurious behavior (NSSI) is a major public health concern. Although widespread, it is yet often a hidden problem. The purpose of this study was to explore the characteristics of self-injurious behavior in youth treated in an in-patient psychiatric unit. Subjects and methods: The study included 105 adolescents with a history of NSSI (mean age 15 years, 80% females) that underwent inpatient psychiatric treatment at a specialized facility. The factors assessed were sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…According to our results, the prevalence of NSSI in female adolescents was higher than that in male adolescents. This was consistent with the research results in a study that NSSI showed to be associated with female gender ( 84 ). Female adolescents may be more susceptible to self-injury because they are more likely to experience higher negative influence and have lower ability to manage emotion, including acceptance of emotions and controlling impulses ( 78 ).…”
Section: Discussionsupporting
confidence: 93%
“…According to our results, the prevalence of NSSI in female adolescents was higher than that in male adolescents. This was consistent with the research results in a study that NSSI showed to be associated with female gender ( 84 ). Female adolescents may be more susceptible to self-injury because they are more likely to experience higher negative influence and have lower ability to manage emotion, including acceptance of emotions and controlling impulses ( 78 ).…”
Section: Discussionsupporting
confidence: 93%
“…Fourteen (64%) studies mentioned methods of self-harm that were seen in a particular culture (Söderberg, 2001;Jacobson et al, 2008;Holm and Severinsson, 2010;Wong et al, 2010;Cerutti et al, 2011;Gratz et al, 2012;You et al, 2012;Hu et al, 2016;Hayashi et al, 2017;Takeuchi et al, 2018;Bježančević et al, 2019;Chartrand et al, 2020;Levine et al, 2020). The total sample size for these studies is 26,095, with 63% (n = 16,313) women and 37% (n = 9,782) men.…”
Section: Methods Of Self-harmmentioning
confidence: 99%
“…Using a reference and citation search from the 12 articles (Jacobson et al, 2008;Nath et al, 2008;Holm and Severinsson, 2010;Wong et al, 2010;Cerutti et al, 2011Cerutti et al, , 2012Gratz et al, 2012;Del Bello et al, 2015;Hu et al, 2016;Hayashi et al, 2017;Takeuchi et al, 2018;Bježančević et al, 2019) identified through the PubMed search, an additional 4 articles (Paris, 1996;Pinto et al, 2000;Söderberg, 2001;Wang et al, 2012) were identified. Five other articles (Bježančević et al, 2019;Ronningstam et al, 2018;Haliczer et al, 2019;Chartrand et al, 2020;Levine et al, 2020) included in the literature review are from non-exhaustive initial searches that were conducted while refining the keywords for the main search. One additional article was discovered by a reviewer and included in the review (You et al, 2012).…”
Section: Literature Searchmentioning
confidence: 99%
“…Of these, 26.7% have already thought about doing something and 19.1% report having done it. Thus, individuals who exhibit self-injury behavior need frequent care and evaluation, since they must be considered as a group with a high risk of suicide (40) .…”
Section: Personal Characteristicsmentioning
confidence: 99%